Traditional Religious Beliefs of Tropical Africa Peoples in the Collections of Kazan University Ethnographic Museum - Titova, Tatyana A.; Gushchina, Elena G.; Frolova, Elena V. (Journal of History Culture and Art Research, 2017)
The interest regarding to African cultural values has intensified in all countries of the African continent in the second half of the twentieth - early twenty-first century. The aim of the article is to analyze the traditional religious beliefs of Tropical Africa peoples. The interdisciplinary approach that allows us to consider social realities in the context of historical and cultural changes has become the leading one to the study of this problem. The article shows the role of religion in African society. They considered the system of traditional beliefs and cults, the main forms of religious beliefs, as well as the diversity of religious attributes and its use on the basis of materials from the museum collection of the Ethnographic Museum of the University. The materials of the article can be useful for ethnologists, anthropologists, museum staff and everyone who is interested in this topic.